Pharmacological analysis of the activation and receptor properties of the tonic GABA(C)R current in retinal bipolar cell terminals. - Stefanie M Jones; Mary J Palmer (PLoS ONE)
GABAergic inhibition in the central nervous system (CNS) can occur via rapid, transient postsynaptic currents and via a tonic increase in membrane conductance, mediated by synaptic and extrasynaptic GABA(A) receptors (GABA(A)Rs) respectively. Retinal bipolar cells (BCs) exhibit a tonic current mediated by GABA(C)Rs in their axon terminal, in addition to synaptic GABA(A)R and GABA(C)R currents, which strongly regulate BC output. The tonic GABA(C)R current in BC terminals (BCTs) is not dependent on vesicular GABA release, but properties such as the alternative source of GABA and the identity of the GABA(C)Rs remain unknown. Following a recent report that tonic GABA release from cerebellar glial cells is mediated by Bestrophin 1 anion channels, we have investigated their role in non-vesicular GABA release in the retina. Using patch-clamp recordings from BCTs in goldfish retinal slices, we find that the tonic GABA(C)R current is not reduced by the anion channel inhibitors NPPB or flufenamic acid but is reduced by DIDS, which decreases the tonic current without directly affecting GABA(C)Rs. All three drugs also exhibit non-specific effects including inhibition of GABA transporters. GABA(C)R ρ subunits can form homomeric and heteromeric receptors that differ in their properties, but BC GABA(C)Rs are thought to be ρ1-ρ2 heteromers. To investigate whether GABA(C)Rs mediating tonic and synaptic currents may differ in their subunit composition, as is the case for GABA(A)Rs, we have examined the effects of two antagonists that show partial ρ subunit selectivity: picrotoxin and cyclothiazide. Tonic and synaptic GABA(C)R currents were differentially affected by both drugs, suggesting that a population of homomeric ρ1 receptors contributes to the tonic current. These results extend our understanding of the multiple forms of GABAergic inhibition that exist in the CNS and contribute to visual signal processing in the retina.